2013
DOI: 10.1039/c3lc41345d
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of glass nanofluidic chips at room temperature by a one-step surface activation using an O2/CF4 plasma treatment

Abstract: A technical bottleneck to the broadening of applications of glass nanofluidic chips is bonding, due to the strict conditions, especially the extremely high temperatures (~1000 °C) and the high vacuum required in the current glass-to-glass fusion bonding method. Herein, we report a strong, nanostructure-friendly, and high pressure-resistant bonding method, performed at room temperature (RT, ~25 °C) for glass nanofluidic chips, using a one-step surface activation process with an O(2)/CF(4) gas mixture plasma tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 15 publications
2
54
0
Order By: Relevance
“…We utilized low‐temperature bonding in order to avoid heat‐associated destruction of functional molecules during thermal bonding. This method enables glass‐glass bonding at 25–100 °C by oxygen plasma surface activation involving fluorine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We utilized low‐temperature bonding in order to avoid heat‐associated destruction of functional molecules during thermal bonding. This method enables glass‐glass bonding at 25–100 °C by oxygen plasma surface activation involving fluorine.…”
Section: Resultsmentioning
confidence: 99%
“…After irradiation, the APTES‐patterned substrate was rinsed with ultrapure water and dried with flowing air. The substrate was bonded with another silica substrate including micro‐ and extended nanochannels in which the surfaces were activated with fluorine‐enhanced plasma, as previously reported . Briefly, after washing with piranha solution, the clean silica substrate with channels was placed in the plasma chamber and treated with fluorine‐containing oxygen plasma (60 Pa O 2 , 250 W power) for 40 sec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Howlader et al reported bonding strengths as high as 20 MPa by treating substrates with a sequential process of plasma activation steps (O 2 RIE and nitrogen radical treatment) prior to the bonding at room temperature [84]. Recently, one-step O 2 /CF 4 plasma treatment [85] and sodium silicate assisted bonding [86] have been reported for low-temperature bonding of glass substrates.…”
Section: Sealing Hard Surfaces Such As Si and Glassmentioning
confidence: 97%
“…Unlike glass-glass bonding, [79] for example, bonding LN to materials other than PDMS is difficult. Unlike glass-glass bonding, [79] for example, bonding LN to materials other than PDMS is difficult.…”
Section: Introductionmentioning
confidence: 99%